Mighty machines. Boats to the rescue - Sv̌ille Pictures; TFO-TVOntario (Firm); Knowledge Network (B.C.); NCircle Entertainment ([Dallas, TX] : Distributed by NCircle Entertainment, 2007)
Patrol the harbor with the police boat. Visit enormous naval ships, ferry boats, and cargo ships. Recover a "man overboard", and more.
To the rescue -- Making waves -- In the harbour.
Title from disc label.
"Running time approximately 90 minutes, including bonus episodes"--Container.
Bonus: 4 five-minute episodes.
Not rated.
DVD.
Keywords: Boats and boating -- Juvenile films; Work boats -- Juvenile films; Search and rescue boats -- Juvenile films; Search and rescue operations -- Juvenile films; Machinery -- Juvenile films; Boats and boating; Work boats; Search and rescue boats; Rescue work; Machinery; Television programs; DVD-Video discs; Children's television programs; Nonfiction television programs; Foreign television programs; Motion pictures, Canadian; DVD-Video discs